Conflicting perspectives on urban landscape quality in six urban regions in Europe and their implications for urban transitions. (December 2022) - Hisschemöller, Matthijs; Kireyeu, Viktar; Freude, Tara; Guerin, Florian; Likhacheva, Olga; Pierantoni, Ilenia; Sopina, Ana; von Wirth, Timo; Šćitaroci, Bojana Bojanić Obad; Mancebo, François; Sargolini, Massimo; Shkaruba, Anton
Abstract: The European Landscape Convention urges countries to involve stakeholders including citizens in the governance of ordinary (urban) landscapes. This paper studies conflicting stakeholder perspectives on urban landscape quality in the context of urban sustainability transitions in six European urban regions in the Netherlands, Italy, France, Croatia, Belarus and the Russian Federation. Repertory grid technique helped to identify the dimensions through which persons evaluate urban landscape quality. Ninety-three (93) interviewees elicited 1400 bipolar constructs, such as "Edible green – Concrete" or "Community, group – Loneliness". They then selected two constructs they consider most relevant in the context of urban sustainability transitions, and ranked all pictures on a 10-points scale. The rankings were analyzed using Multiple Correspondence Analysis. We find that, in spite of the many social and cultural differences between the regions, stakeholders largely agree on the preferred direction of urban transitions; more green and blue spots where people can meet and undertake joint (leisure) activities. The main conflict is between, on the one hand, a preference for organized development and beautification and, on the other hand, naturalness (permeability of soil) and organic development. The paper considers several challenges for transition governance. Highlights: Landscape transitions come with conflicting perspectives on urban landscape quality. Citizens need to participate in the governance of ordinary urban landscapes. Stakeholders largely agree on the preferred direction of urban transitions. Landscape development tend to conflict with climate change resilience. Urban escape poses a threat to the bottom-up governance of urban landscapes.